Theorizing Artificial Intelligence as an Organizational Actor: Insights from a Narrative Review (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This narrative review examines how artificial intelligence (AI) is being theorized as an organizational actor within management and organization studies. The paper synthesizes fragmented theoretical perspectives to develop an integrated conceptual framework that identifies the antecedents, mechanisms, and contextual conditions shaping AI organizational actorhood. A systematic search of Web of Science was conducted, yielding 47 peer-reviewed articles published between 2020 and 2026. The selected literature spans management, business, and accounting disciplines. Through thematic analysis guided by institutional theory, agency theory, and sociomateriality, the review critically synthesizes scholars' conceptualizations of AI's organizational actorhood and proposes a testable conceptual framework. Four key themes emerge: (1) AI as an institutional actor subject to and generative of institutional pressures; (2) AI as an economic agent with principal-agent dynamics; (3) AI as a socio-material ensemble co-constituting organizational realities; and (4) AI's evolving autonomy from tool to quasi-autonomous actor. The review reveals that, while AI is increasingly theorized to possess agentic qualities, conceptualizations remain fragmented across theoretical silos. This review contributes a multi-dimensional framework for theorizing AI organizational actorhood that integrates institutional, economic, and socio-material perspectives. It identifies five antecedents, three moderators, three mediators, and four control variables that collectively shape the emergence of AI as an organizational actor. For managers and policymakers, recognizing AI as an organizational actor with emergent agency necessitates rethinking governance mechanisms, accountability structures, and legitimacy strategies. This is the first narrative review to propose a comprehensive, testable conceptual framework for AI organizational actorhood, synthesizing diverse theoretical traditions to advance a coherent research agenda.